Transcriptomic analyses reveal increased expression of dioxygenases, monooxygenases, and other metabolizing enzymes involved in anthracene degradation in the marine alga Ulva lactuca - González, Alberto; Osorio, Héctor; Romero, Stephanie; Méndez, Patricia; Sepúlveda, Muriel; Laporte, Daniel; Gutierrez-Cutiño, Marlen; Santander, Rocío; Castro-Nallar, Eduardo; Moenne, Alejandra (Frontiers in Plant Science, 2022)
To analyze the mechanisms involved in anthracene (ANT) degradation in the marine alga Ulva lactuca, total RNA was obtained from the alga cultivated without ANT and with 5 μM of ANT for 24 h and transcriptomic analyses were performed. A de novo transcriptome was assembled, transcripts differentially expressed were selected and those overexpressed were identified. Overexpressed transcripts potentially involved in ANT degradation were: one aromatic ring dioxygenase, three 2-oxoglutarate Fe (II) dioxygenases (2-OGDO) and three dienelactone hydrolases that may account for anthraquinone, phthalic anhydride, salicylic acid and phthalic acid production (pathway 1). In addition, two FAD-dependent monooxygenases, four cytP450 monooxygenases, one epoxide hydrolases, one hydroxyphenylpyruvic acid dioxygenase and two homogentisic acid dioxygenases (HGDO) were identified that may also participate in ANT degradation (pathway 2). Moreover, an alkane monooxygenase (alkB), two alcohol dehydrogenases and three aldehyde dehydrogenases were identified which may participate in linear hydrocarbons degradation (pathway 3). Furthermore, the level of transcripts encoding some of mentioned enzymes were quantify by qRT-PCR are in the alga cultivated with ANT for 0 to 48 h, and those more increased were 2-OGDO, HGDO and alkB monooxygenase. Thus, at least three pathways for ANT and linear hydrocarbons degradation may be exist in U. lactuca. In addition, ANT metabolites were analyzed by GC-MS allowing the identification of anthraquinone, phthalic anhydride, salicylic acid and phthalic acid, thus, validating the pathway 1.